2021
DOI: 10.3390/ijms22136971
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Enhanced Asp-Rich Antimicrobial Peptides: N-Terminal Coordination by Zn(II) and Cu(II), Which Distinguishes Cu(II) Binding to Different Peptides

Abstract: The antimicrobial activity of surfactant-associated anionic peptides (SAAPs), which are isolated from the ovine pulmonary surfactant and are selective against the ovine pathogen Mannheimia haemolytica, is strongly enhanced in the presence of Zn(II) ions. Both calorimetry and ITC measurements show that the unique Asp-only peptide SAAP3 (DDDDDDD) and its analogs SAAP2 (GDDDDDD) and SAAP6 (GADDDDD) have a similar micromolar affinity for Zn(II), which binds to the N-terminal amine and Asp carboxylates in a net ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…They seem to utilize metal ions and the negatively charged components of the microbial membrane to form salt bridges, thus interacting with microbes [ 88 ], which are similar to the charge-neutralization characteristics of larger proenzyme [ 89 ]. For example, ovine pulmonary surfactant associated anion peptide (SAAP), the first discovered anionic AMP with 5–7 aspartate residues, had antimicrobial activity to the ovine pathogen Mannheimia haemolytica in the presence of Zn ions [ 90 ]. When 0.14 mol/L NaCl and EDTA were added into the surfactant solution, its bactericidal activity was largely inhibited, while restored when ZnCl 2 was replenished.…”
Section: Structure and Characteristics Of Ampsmentioning
confidence: 99%
“…They seem to utilize metal ions and the negatively charged components of the microbial membrane to form salt bridges, thus interacting with microbes [ 88 ], which are similar to the charge-neutralization characteristics of larger proenzyme [ 89 ]. For example, ovine pulmonary surfactant associated anion peptide (SAAP), the first discovered anionic AMP with 5–7 aspartate residues, had antimicrobial activity to the ovine pathogen Mannheimia haemolytica in the presence of Zn ions [ 90 ]. When 0.14 mol/L NaCl and EDTA were added into the surfactant solution, its bactericidal activity was largely inhibited, while restored when ZnCl 2 was replenished.…”
Section: Structure and Characteristics Of Ampsmentioning
confidence: 99%
“…Given that the crystallisation conditions contain ZnCl 2 , we postulate the metal ions to be Zn 2+ . Indeed, peptides that are aspartate-rich have been shown to bind to zinc ions (Miller et al, 2021), and in the structure, the ions are tetrahedrally coordinated by carboxyl groups of the aspartate side chains, oxygen groups of the phosphoserine, and water molecules ( Figure 3D ). The co-ordination geometry and bond lengths are consistent with zinc binding (∼2.0 Å in the structure) and were supported by using the CMM metal binding site validation server (Zheng et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphate inhibits their bactericidal activity, while Ca(II) and Mg(II) were found to have no effect. Zn(II) is required in the antimicrobial activity against K. pneumoniae, E. coli, S. aureus, S. faecalis, Pasteurella haemolytica, and Mannheimia haemolytica [94,96]. Though, only P. haemolytica and Mannheimia had MIC values in the low micromolar range [94,96].…”
Section: Surfactant-associated Anionic Peptides (Saaps)mentioning
confidence: 99%
“…Zn(II) is required in the antimicrobial activity against K. pneumoniae, E. coli, S. aureus, S. faecalis, Pasteurella haemolytica, and Mannheimia haemolytica [94,96]. Though, only P. haemolytica and Mannheimia had MIC values in the low micromolar range [94,96]. The bioactivity of synthetic aspartic acid polymers was also tested, and it was observed that the MIC of these peptides was proportional to the number of Asp residues and that Zn(II) was still required for their bactericidal functionality [94].…”
Section: Surfactant-associated Anionic Peptides (Saaps)mentioning
confidence: 99%